The rise of the Republican right from Goldwater to Reagan - Conley, Brian M. (Routledge, 2019)
"Few scholars have paid close attention to the factors internal to the Republican Party that helped the Right to consolidate its power within the party between the 1960s and the 1980s. Plugging the gap in party literature, The Rise of the Republican Right from Goldwater to Reagan provides a comprehensive account of the rise of the Republican Right in the years between Barry Goldwater's 1964 presidential defeat and the election of Ronald Reagan as president in 1980. Specifically, it offers a historical-institutional analysis of the organizational factors internal to the Republican Party that helped the conservative Right maintain, and then expand its ascendant position within the GOP in the critical years between Goldwater and Reagan. Brian M. Conley demonstrates how the growth of the Right during this period was aided by a desire on the part of many Republican leaders to rebound from electoral defeat by rebuilding the party organizationally, rather than reforming it politically, through the introduction of a more 'service' oriented party structure. The Rise of the Republican Right will interest academics, party scholars and researchers eager to gain a more nuanced understanding of the factors that helped the Right become a dominant force within the Republican Party"--
Keywords: Republican Party (U.S. : 1854- ) / History / 20th century; Conservatism / United States / History / 20th century; Right and left (Political science) / United States / History / 20th century